House prices and economic growth in Asia Pacific / Nurfaziera Mohd Yeb - Mohd Yeb, Nurfaziera (Faculty of Business and Management, 2018)
This study attempts to examine the roles of the house prices and economic growth in Asia Pacific by using gross domestic product (GDP) as dependent variable and gross capital formation (GCF), labor force (LF), house prices index (HPI), consumption (CMP), stock prices (SP), money supply (MS) and unemployment (UNEMR) as independent variables in panel data structure. To conduct this analysis, several tests have been applied such as stationary test, descriptive analysis, multicollinearity test, panel regression, normality test and autocorrelation test. The panel data covers a sample formed from 12 countries and annual observation for 37 years from 1980 to 2016. However, after execute data cleaning; the sample would be 9 countries and annual observation for 10 years from 2006 to 2015 in Asia Pacific. The main focus is to study the significant relationship between independent variables and dependent variables and the results has shown that all independent variables have significant relationship with dependent variable.